Trapeziometacarpal Joint Arthroplasty of the Thumb without Osseous Tunnels and Carpal Tunnel Release via a Radial Approach; Technique, and Results - Chan, Chung Ming; Cisneros, Efraín Farías; Tsai, Tsu-Min (The Surgery Journal, 2019)
Background Numerous surgeries have been described for osteoarthritis of the trapeziometacarpal (TMC) joint. We describe the senior author's experience with his technique of concurrent arthroplasty of the TMC joint, and carpal tunnel release (CTR) via a radial approach.Methods The study is a case series of patients managed over a 3-year period. We included 86 patients over 40 years of age that had concurrent CTR. We used the paired t-test to compare the preoperative and postoperative grip strength and functional scoring (including the Levine-Katz questionnaire for carpal tunnel syndrome, disabilities of the arm shoulder and hand [DASH] score and QuickDASH9).Results Mean age at surgery was 62.8 years, and mean follow-up was 13.1 months. Functional outcomes were analyzed in 65 patients. Grip strength returned to the preoperative measurement by 3 months. Analysis of the nine patients followed up for more than 13 months postoperatively showed a significant increase in grip strength at last follow-up. The grip strength in both hands was also similar beyond 13 months. Significant decreases in the functional scores recorded indicated a reduction in disability, symptom severity, and functional impairment.Conclusions In conclusion, we present the favorable results of this technique of TMC arthroplasty and CTR involving no bone tunnels and short-term immobilization.
Keywords: arthritis; arthroplasty; carpometacarpal joint; thumb; trapeziectomy